Ultrastructural GABA immunocytochemistry in the mossy fiber terminals of Wistar and genetic absence epileptic rats receiving amygdaloid kindling stimulations - AKAKIN, DİLEK; ONAT, FİLİZ; GÜLÇEBİ İDRİZ OĞLU, MEDİNE; KAYA, ÖZLEM TUĞÇE; GÜLHAN, REZZAN; ŞİRVANCI, SERAP; KARAMAHMUTOĞLU, TUĞBA (ELSEVIER, 2011)
The existence of absence epilepsy and temporal lobe epilepsy in the same patient is not common in clinical practice. The reason why both types of seizures are rarely seen in the same patient is not well understood. Therefore, we aimed to investigate kindling in a well known model of human absence epilepsy, genetic absence epilepsy rats from Strasbourg (GAERS). In the present study, we analyzed whether the GABA content of GAERS that received kindling stimulations was altered in the hippocampal mossy fiber terminals compared to non-epileptic control (NEC) Wistar rats. For this purpose, we used an immunocytochemical technique at the ultrastructural level. Ultrathin sections were immunolabeled with anti-GABA antibody and transmission electron microscopy was used for the ultrastructural examination. The number of gold particles per nerve terminal was counted and the area of the nerve terminal was determined using NIH image analysis program. The GABA density was found to be higher in sham-operated GAERS than sham-operated Wistar rats. The density was increased in kindling Wistar group compared to sham-operated Wistar and kindling GAERS groups. No statistical difference was observed between sham-operated GAERS and kindling GAERS groups. The increase in GABA levels in stimulated Wistar rats may be a result of a protective mechanism. Furthermore, there may be strain differences between Wistar rats and GAERS and our findings addressing different epileptogenesis mechanisms in these strains might be a basis for future experimental studies. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: GAERS; Hippocampus; Mossy terminal; GABA; Immunocytochemistry; IDIOPATHIC GENERALIZED EPILEPSY; GRANULE CELLS; GLUCOCORTICOID ENDANGERMENT; GABAERGIC PHENOTYPE; WAVE DISCHARGES; DENTATE GYRUS; TEMPORAL-LOBE; GLUTAMATE; SEIZURES; HIPPOCAMPUS